PENDEKATAN SAINTIFIK DALAM KURIKULUM MERDEKA DI SDN KOWANG II KABUPATEN TUBAN: (Mata Pelajaran Ilmu Pengatahuan Alam IPA) - Ma'rifah, Dina; Rakhma W, Ifa Seftia (ISTIQRA: Jurnal Hasil Penelitian, 2023)
The scientific approach is categorized as a learning process that can guide students in solving problems. Problem solving can be done by planning activities, collecting data, and analyzing data to produce a conclusion. Based on this explanation, this research aims to determine students' learning outcomes in class IV of SDN Kowang II, especially in science subjects with the theme of scientifically based forms of matter and their changes in the era of the independent curriculum. Therefore, this research uses descriptive qualitative methods. The type of research used is classroom action, which is carried out in two cycles, each starting with the planning, implementation, observation, and reflection stages. So the results of this research show that at least 80% of class IV students obtained learning outcomes in accordance with the minimum completeness criteria (KKM), namely 70. The increase learning outcomes in each cycle increased, namely in cycle I at 77,8% and cycle II at 85,20%. This shows that the completion of class IV learning outcomes has reached indicators of success, so it can be concluded that implementing scientific-based experimental methods in the independent curriculum, especially in science subjects, can improve students' classical learning outcomes